(untitled) (Cybersecurity and Network Defense Research, 2023)
Secure software development is crucial in today’s digital landscape to mitigate vulnerabilities and reduce the risk of cyber attacks. This research paper explores best practices for secure software development, including secure coding practices, threat modeling, vulnerability assessment, and secure deployment strategies. The paper also discusses the importance of integrating security throughout the software development lifecycle (SDLC) and highlights the role of developers, security professionals, and organizations in ensuring software security. By implementing these best practices, developers can enhance the security posture of their applications and protect sensitive data from unauthorized access and exploitation.